Characteristics and bioinformatics of peptides from natural and cultured sandfish (Holothuria scabra) - Pawitporn Daopa; Chakkapat Aenglong; Sittiruk Roytrakul; Teerasak E-kobon; Xue Zhao; Wanwimol Klaypradit (Food Chemistry: Molecular Sciences)
This study aimed to investigate the characteristics and bioinformatics identification of peptides in sandfish (Holothuria scabra) protein hydrolysate from natural and cultured sources, with the hypothesis that different sources of sandfish and enzymatic treatments would result in distinct peptide profiles. Sandfish from both sources were subjected to double enzymatic hydrolysis using neutral protease–alcalase (NA), papain–neutral protease (PN), and papain–alcalase (PA) to obtain protein hydrolysates. The hydrolysates were analyzed for amino acid composition, protein molecular weight distribution, functional groups using FTIR spectroscopy, LC-MSMS analysis coupled with bioinformatics for protein and peptide identification, and mineral profile. The resulting hydrolysates exhibited similar amino acid profiles, characterized by high levels of glycine, alanine, glutamic acid, and aspartic acid. The functional groups of the sandfish protein hydrolysates were primarily found at wavenumbers 1658 cm−1 (amide I), 1541 cm−1 (amide II), and 1246 cm−1 (amide III). Peptides with molecular weights below 500 Da predominated in every sample, highlighting their small molecular size. LC-MSMS analysis, coupled with bioinformatics database comparisons, indicated that sandfish from natural and cultured sources, as well as different enzymes used in the hydrolysis process, significantly affect protein and peptide pattern. Of the 2132 identified proteins, 1258 exhibited significant differences (p < 0.05, FDR < 0.05). This study provides insights into how source and enzymatic treatment influence peptide profiles, which could be applied in the development of functional ingredients or bioactive peptides from sandfish.